Analisis Dan Simulasi Persamaan Differensial Pada Pemodelan Penyakit Campak di Kota Pare-pare - Syafruddin Side; Rahmat Syam; Meisy Tri Elsa (Jurusan Matematika FMIPA UNM, 2018)
This research discusses the SEIRV model of measles. The data used is the number of people with measles in Parepare City in 2015. This data is obtained from Parepare City Health Department. The discussion begins with constructing the SEIRV model of measles,determining the equilibrium point and analyzing the stability. Then, creating a simulation model. This research is conducted by using method of literature study. It is expected to proside an overview of the SEIRV mathematical model. The steps taken are identifying the problem, formulating assumptions to obtained, vaccination is the best way to cure measles